SURVEI PENILAIAN LKPD UNTUK MENINGKATKAN PEMAHAMAN PADA MATERI SIKLUS MAKHLUK HIDUP SISWA SEKOLAH DASAR - Yayuk Cicilia; Rian Vebrianto (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2020)
This study aims to determine the effectiveness of the use of LKPD to increase students' understanding of the science material, namely the cycle of living things on theme 6. This type of research is a survey study using a questionnaire distributed to 40 respondents in grade V of SDN 193, Pekanbaru City. Data were analyzed using SPSS. From the research conducted shows the use of LKPD with the approach used is a quantitative approach that provides many benefits to students' understanding of science material that is the cycle of living things on theme 6. This can be seen from the average value obtained indicating that respondents generally answered yes or agree to the statement given. The use of LKPD with a scientific approach can increase students' motivation to learn and understand the life cycle material.